AMF promotes the structure and metabolic activity of rhizosphere soil microbial communities in areca/vanilla intercropping system under nitrogen-limited conditions - Zhuang, Huifa; Feng, Zhuo; Hu, Yunbin; Ning, Ziwei; Zhao, Qingyun; Wang, Hui; Xing, Yizhang; Zhang, Ang (Frontiers in Microbiology, 2025)
This study systematically investigated the response mechanisms of the rhizosphere microenvironment and physiological metabolism in an areca/vanilla intercropping system under three nitrogen reduction levels (conventional, 30% reduction, and 60% reduction) combined with inoculation of two arbuscular mycorrhizal fungi (AMF). The results showed that under 30% nitrogen reduction, inoculation with Claroideoglomus etunicatum significantly increased soil hydrolytic nitrogen by 26.29% (P < 0.05), this change directly drives the increase in nitrate reductase activity and photosynthetic pigment synthesis in plant leaves by optimizing the microenvironment of root nitrogen supply. Funneliformis mosseae increased soil organic matter by 10.93% (P < 0.05) by enriching the rhizosphere carbon source pool, reshaping the microbial interaction network, and indirectly promoting physiological metabolism related to root nutrient absorption. AMF exhibited species-specific regulation of soil enzyme activities. For instance, under conventional fertilization, Claroideoglomus etunicatum increased phosphatase activity by 25.68% (P < 0.05) by enhancing the biochemical microenvironment of organic phosphorus mineralization in the rhizosphere, thereby providing substrates for plant phosphorus metabolism. While under 60% nitrogen reduction, Funneliformis mosseae boosted urease activity by 64.46% (P < 0.05). This response stems from its induction of the enrichment of urease-producing bacterial communities in the rhizosphere, accelerating the conversion of organic nitrogen to alleviate nitrogen metabolic stress in plants under low nitrogen stress. Additionally, nitrogen reduction combined with AMF inoculation significantly promoted the accumulation of glomalin-related soil protein (GRSP). At 60% nitrogen reduction treatment, compared with the control group without AMF inoculation, the treatment group inoculated with Funneliformis mosseae showed a 5.16% (P < 0.05) increase in GRSP. This study demonstrates that AMF optimizes rhizosphere nutrient cycling (e.g., AMF (C.e) significantly increases hydrolytic nitrogen by 26.29% (P < 0.05) under 30% nitrogen reduction) and improves soil structure (e.g., AMF (F.m) promotes GRSP accumulation by 5.16% (P < 0.05), providing a theoretical basis for reducing fertilizer application and promoting sustainable intensification of tropical intercropping systems.